Effect of focal spot scanning method in agarose gel and chicken breast on heating efficiency in cavitation-enhanced ultrasonic heating. (26th April 2021) - Ueda, Kohei; Ito, Sayaka; Umemura, Shin-ichiro; Yoshizawa, Shin
Abstract: High-intensity focused ultrasound (HIFU) treatment is a non-invasive method of cancer treatment. In a HIFU treatment, ultrasound is focused on a target tumor tissue leading to temperature rise that coagulates the tissue. The treatment has a problem of long treatment time because a tumor is usually larger than the focal spot of HIFU. To reduce the treatment time, cavitation bubbles can be used for accelerating ultrasonic heating. Additionally, the heat conducting away from a focal spot can be utilized by properly scanning the focus. In this study, three sequences of scanning the focus to form six foci were compared by observing cavitation bubbles and measuring temperature rise in an excised chicken breast tissue and an agarose gel as well as a thin slice of tissue sandwiched between agarose gels. The results showed that there were differences in the behavior of bubbles and the efficient sequence between the tissue and the gel.